2018
DOI: 10.1039/c7ay02694c
|View full text |Cite
|
Sign up to set email alerts
|

A new wipe-sampling instrument for measuring the collection efficiency of trace explosives residues

Abstract: Trace explosives detection, a crucial component of many security screening environments, commonly employs wipe-sampling. Since collection of an explosive residue is necessary for detection, it is important to have a thorough understanding of the parameters that affect the efficiency of collection. Current wipe-sampling evaluation techniques for explosive particles have their limits: manual sampling (with fingers or a wand) is limited in its ability to isolate a single parameter and the TL-slip/peel tester is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Experimental details for these procedures may be found in several recent publications. 12–14 Briefly, explosive particle deposits were inkjet printed as 8 × 8 spot liquid droplet arrays, with a total mass loading of 350 ng, onto 1 cm by 1 cm square Bytac strips (Teflon film with foil backing, BytacBench and Shelf Protector Sheets, SPI Supplies and Structure Probe, West Chester, PA) using a JetLab 4XL inkjet printer (MicroFAB, Plano, TX) and a 1 mg mL −1 acetonitrile standard solution of 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) (Cerilliant Corp., Round Rock, TX). After printing, the arrays were dried to create solid explosive particle residues which were then transferred to the test surface using a dry transfer protocol.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental details for these procedures may be found in several recent publications. 12–14 Briefly, explosive particle deposits were inkjet printed as 8 × 8 spot liquid droplet arrays, with a total mass loading of 350 ng, onto 1 cm by 1 cm square Bytac strips (Teflon film with foil backing, BytacBench and Shelf Protector Sheets, SPI Supplies and Structure Probe, West Chester, PA) using a JetLab 4XL inkjet printer (MicroFAB, Plano, TX) and a 1 mg mL −1 acetonitrile standard solution of 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) (Cerilliant Corp., Round Rock, TX). After printing, the arrays were dried to create solid explosive particle residues which were then transferred to the test surface using a dry transfer protocol.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A robotic wipe-sampling instrument, based on a repurposed Robo3D fused deposition modelling (FDM) printer (Robo3D, San Diego, CA), was used to complete the swiping experiments as a function of the mass placed on the mount holding the sampling wipe with values ranging from 260 g to 1060 g (applied load of 2.6 N to 10.4 N) using a translational velocity of 5 cm s −1 over a total travel distance of 12 cm. 14 Both this and the Bytac strip used for manual deposition of the explosive particles onto the test surface and the wipe (TCF or CN) were set aside for quantitation. Previous results have demonstrated that the slip/peel tester described previously, and the robot sampling system (which uses the same mounting hardware) provide equivalent results.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective wipe- or swab-based processes for the removal of particulate matter from surfaces are important for applications such as trace contraband detection, toxic substance sampling, and dust removal and cleaning. In many applications, ineffective particle collection can have serious repercussions, including national security risks (failure to detect explosives at security checkpoints) and public health emergencies (failure to detect chemical warfare agents or toxic metals). Despite these consequences, wipes used in trace detection typically collect only a small fraction of particles present on a given surface.…”
Section: Introductionmentioning
confidence: 99%